The In Vitro Effects of Choline on Non-Esterified Fatty Acid-Treated Bovine Peripheral Blood Leukocytes - Li, Cheng-Yan; Chen, Yueh-Tung; Moonmanee, Tossapol; Chan, Jacky Peng-Wen; Wang, Chien-Kai (Animals (Basel), 2025)
The transition period is defined as 3 weeks around parturition, involving the rapid increase in the energy demand, promoting adipose mobilization and non-esterified fatty acid (NEFA) release. High NEFA levels might cause oxidative stress and associated health risks, including the disruption of the immune capability of peripheral leukocytes. Nutrient supplementation of choline, which improves cellular lipid metabolism and controls lipid oxidation, potentially maintains the integrity of peripheral leukocytes and alleviates the impacts of increased NEFAs. This study investigated the effects of choline on bovine peripheral blood leukocytes (PBLs) treated with high levels of NEFAs. Peripheral blood mononuclear cells (PBMCs) and polymorphonuclear leukocytes (PMNs) were isolated from dry cows, and treated with 1 mM NEFA in combination with 0, 4, or 12 μM choline. The expression of pro-inflammatory cytokines and oxidative stress indicators was determined. This study demonstrates that 1 mM NEFA induces lipid oxidation and pro-inflammatory cytokine expression in PBLs. Supplementation with 4 μM and 12 μM choline significantly reduced NEFA-induced lipid oxidation; however, it did not affect pro-inflammatory cytokine mRNA expression. In conclusion, choline supplementation may help alleviate NEFA-induced oxidative stress in bovine peripheral blood leukocytes, highlighting its potential as a functional supplement during the transition period. However, it had no observable effect on mitigating pro-inflammatory responses, indicating that additional strategies may be needed to address NEFA-induced immune activation.